A taxonomic revision of the genus Phyxioschema (Araneae, Dipluridae), I: species from Thailand - Schwendinger, Peter J. (Zootaxa, 2009)
Phyxioschema suthepium Raven & Schwendinger, 1989 is revised and additional taxonomic characters and localities are given. Males and females of five new species are described: Phyxioschema erawan sp. n. (northern and western central Thailand), P. huberi sp. n. (southern Thailand), P. sayamense sp. n. (southern Thailand), P. eripnastes sp. n. (southern Thailand) and P. spelaeum sp. n. (southern Thailand). Notes are given on habitat, phenology and reproductive behaviour of all these species. Taxonomic characters are discussed and considerable variation in the genitalia of some species is shown. An hypothesis on the relationships between the currently known Phyxioschema species is presented.